On a Nonlinear Volterra-Fredholm Integral Equation - Pachpatte, B. G. (Sarajevo Journal of Mathematics, 2024)
In this paper we study the existence, uniqueness and other properties of solutions of a certain nonlinear Volterra-Fredholm integral equation. The well known Banach fixed point theorem and the new integral inequality with explicit estimate are used to establish the results. 2000 Mathematics Subject Classification. 34K10, 35R10